Coal-based negative electrode material and preparation method thereof
Through coal-rock screening and efficient ash removal treatment, the problem of unstable performance of coal-prepared negative electrode materials in the existing technology has been solved, and the performance and battery performance of coal-based negative electrode materials have been significantly improved, achieving efficient utilization of coal.
Patent Information
- Application Number
- CN202310791612.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-06-30
AI Technical Summary
The prior art lacks efficient screening and ash removal scheme when preparing negative electrode materials in coal, resulting in unstable performance of coal-based negative electrode materials and ash enrichment reduces material quality.
Coal with inert mass content in coal is screened by coal petrology analysis, and ash removal treatment, including chemical method or physical and chemical combination method, reduce the ash content to less than 0.1%, and then carbonization is carried out to prepare coal-based Negative electrode material.
Efficient screening and ash removal of coal-based negative electrode materials is achieved, significantly improving the performance of the material, battery capacity and first-time Coulomb efficiency, and reducing the negative impact of ash on battery performance.
Smart Images

Figure BDA0004313774240000081 
Figure BDA0004313774240000091 
Figure BDA0004313774240000092
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of carbon materials, and in particular to a coal-based negative electrode material and a preparation method thereof. Background Art
[0002] my country has a large coal consumption and high carbon dioxide emissions. If we want to achieve the peak of carbon emissions by 2030, the use of coal as a traditional fuel will be limited. In order to seek efficient use of coal in the low-carbon era, the development of coal-based carbon material technology has become a hot topic in the research field of the coal industry.
[0003] CN114789998A discloses a negative electrode material and a preparation method thereof and a battery, wherein a coal-based material is prepared by high-temperature treatment, mixed with graphite, and then homogenized under high pressure, and sprayed to prepare a composite powder of the coal-based material and graphene, which has excellent sodium storage performance.
[0004] CN105185997A discloses a sodium ion secondary battery negative electrode material and a preparation method and use thereof. The material is an amorphous carbon material, which is obtained by high-temperature cracking of coal as the main raw material: coal and a hard carbon precursor are used as raw materials, a solvent is added, and then mechanically mixed, dried, and then cross-linked, cured, and cracked in an inert atmosphere.
[0005] CN113493193A discloses an amorphous carbon material and a preparation method thereof, a sodium ion battery negative electrode and a sodium ion battery. The amorphous carbon material is obtained by purifying coal to make the ash content of the coal less than 10%, and then granulating, extracting and carbonizing the coal, and the amorphous carbon material is suitable for use in sodium ion batteries.
[0006] Considering the complex formation conditions of coal, the variety of types and structural properties, which will greatly affect the performance of coal-based negative electrode materials, there is still a lack of efficient technical solutions for the current selection of coal to prepare negative electrode materials. For example, CN114789998A and CN105185997A do not select the type of coal used; while CN113493193A mainly selects coal based on its macroscopic properties rather than its structural characteristics, such as selecting clean coal with a volatile matter of 10-50wt.%, a caking index of <50, and an ash content of <10wt.%, and then performing solvent extraction on the clean coal, and then carbonizing the residue to prepare the negative electrode material. In addition, the ash in the residue will be enriched, thereby reducing the quality and performance of the carbon material. Summary of the invention
[0007] The purpose of the present invention is to provide a coal-based negative electrode material and a preparation method thereof, which can screen out the types of coal suitable for preparing the coal-based negative electrode material from the source, thereby achieving efficient utilization of coal.
[0008] To achieve the above-mentioned object of the invention, the present invention provides a method for preparing a coal-based negative electrode material, comprising the following steps:
[0009] (1) Coal with an inert content of more than 40% in its maceral components is used as screening coal;
[0010] (2) deashing the screened coal to obtain deashed coal;
[0011] (3) Carbonizing the deashed coal to obtain a coal-based negative electrode material.
[0012] Compared with the prior art, the present invention has the following advantages:
[0013] 1. The present invention screens the coal used for preparing the coal-based negative electrode material through coal petrological analysis, requiring that the content of the inert group in the screened coal is greater than 40%, thereby determining the characteristics of the coal used for preparing the coal-based negative electrode material;
[0014] Second, the present invention efficiently removes ash from the screened coal that meets the requirements, and the ash content of the removed coal is reduced to less than 0.1%;
[0015] 3. The present invention can screen out coal that is more suitable for preparing coal-based negative electrode materials, and then prepare the coal-based negative electrode materials through existing processes to achieve efficient utilization of coal. DETAILED DESCRIPTION
[0016] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0017] Unless otherwise specified, the materials and instruments used in the embodiments of the present invention can be obtained from commercial channels.
[0018] The present invention provides a method for preparing a coal-based negative electrode material, comprising the following steps:
[0019] (1) Coal with an inert content of more than 40% in its maceral components is used as screening coal;
[0020] (2) performing ash removal treatment on the screened coal to obtain ash-removed coal;
[0021] (3) Carbonizing the deashed coal to obtain a coal-based negative electrode material.
[0022] In the present invention, the coal microscopic components in step (1) are the components of coal under a microscope, including vitrinite, inertinite, exinite and mineral group.
[0023] Those skilled in the art can understand that the vitrinite is formed by gelation of plant residues, the inertinite is formed by carbonization, the exinite is formed by lipid substances in plant remains, and the mineral group is mainly derived from inorganic minerals in coal.
[0024] Furthermore, the inorganic minerals are the main components of coal ash and will be removed during the ash removal process.
[0025] Those skilled in the art can understand that the volatile matter yield of the exinite group is the highest, followed by the vitrinite group, and the inertinite group is the lowest. This is because the chain compounds with low thermal decomposition resistance account for a large proportion of the exinite group, while the inertinite group is mainly composed of condensed aromatic structures with strong thermal decomposition resistance, and the vitrinite group is between the two.
[0026] In the present invention, the calculation method of the inert group content in step (1) is: 惰质组 / (M 镜质组 +M 惰质组 +M 壳质组 );
[0027] Among them, M 惰质组 is the volume content of inertinite in the coal macerals, M 镜质组 is the volume content of vitrinite in the coal macerals, M 壳质组 It is the volume content of exinite in the coal maceral components.
[0028] In the present invention, the inertinite content is the content of inertinite in the coal microscopic components without considering the mineral groups in the coal microscopic components, and the sum of the contents of vitrinite, inertinite and exinite is taken as the total content 100%, and the calculated inertinite content accounts for the coal microscopic components.
[0029] Furthermore, the content of inertinite, vitrinite and exinite in the coal microscopic components can be obtained by analysis and detection according to the national standards GB / T 16773-2008 (method for preparing samples for coal rock analysis) and GB / T 8899-2013 (method for grouping and mineral determination of coal microscopic components).
[0030] In the present invention, the screened coal in step (1) is coal with an inertin content greater than 40%, preferably coal with an inertin content greater than 50%, more preferably coal with an inertin content greater than 60%, and most preferably coal with an inertin content greater than 70%.
[0031] The inventors of the present application have discovered that when the inertin content in coal is greater than 40%, the coal-based negative electrode material prepared after ash removal has excellent performance. This is because the inertin content in the carbonization stage is low, and after carbonization treatment, it is more conducive to the formation of a relatively uniform and stable structure of the coal-based negative electrode material, and the influence of the residual vitrinite and exinite after carbonization is significantly reduced.
[0032] The present invention does not limit the method of removing ash in step (2), which may be a physical method, a chemical method, or a combination of physical and chemical methods in the art.
[0033] In some embodiments, in order to reduce the ash content in the deashed coal as much as possible and reduce the impact of the chemical components in the ash on the product coal-based negative electrode material, the deashing method in step (2) is preferably a chemical method, or a combination of physical and chemical methods.
[0034] Those skilled in the art will appreciate that, among the chemical methods, the hydrofluoric acid method (HF / HCl) has the highest dust removal efficiency, but hydrofluoric acid is harmful to the human body and the environment, and can corrode equipment materials and factory buildings, so conventional acids and alkalis can be used instead of hydrofluoric acid.
[0035] Furthermore, the conventional acid and alkali are conventional acids for coal ash removal such as hydrochloric acid, sulfuric acid, and nitric acid, and conventional alkalis for coal ash removal such as sodium hydroxide and potassium hydroxide.
[0036] In some embodiments, the conventional acid-base method can be used to remove coal ash using a combination of HCl / NaOH, a combination of HNO3 / NaOH, and a combination of H2SO4 / NaOH.
[0037] Those skilled in the art can understand that although the ash removal efficiency of the conventional acid-base method is not as good as that of the hydrofluoric acid method, the conventional acid-base method has obvious advantages in terms of economic and environmental benefits, and under certain conditions, the ash removal effect of the conventional acid-base method can be equivalent to that of the hydrofluoric acid method.
[0038] In some embodiments, the ash content of the deashed coal in step (2) can be reduced to 0.5%, preferably less than 0.2%, and more preferably less than 0.1%.
[0039] Those skilled in the art can understand that the coal-based negative electrode material made from deashed coal with low ash content can effectively avoid the charge / discharge inert elements in the ash acting as invalid components leading to reduced battery performance, as well as harmful elements in the ash (such as Fe) interacting with the positive and negative electrodes and the electrolyte, increasing the risk of battery use and reducing battery life.
[0040] In some embodiments, the deashed coal may be ground before carbonization to a particle size of D 50 =1-100 μm, preferably 2-50 μm, more preferably 3-25 μm.
[0041] The inventors of the present application have found that a preferred particle size can improve the capacity and first coulombic efficiency (first efficiency) of the coal-based negative electrode material.
[0042] Furthermore, the grinding process only needs to ensure that the particle size D of the coal-based negative electrode material is50 The timing of the grinding process is not limited as long as the requirements are met. For example, the grinding process can also be performed after the carbonization in step (3), and the particle size requirement remains unchanged.
[0043] In some embodiments, in step (3), the carbonization temperature is 600-2200° C., and the carbonization time is 0.1-50 h;
[0044] Preferably, the carbonization temperature is 700-2100°C, and the carbonization time is 0.5-40h;
[0045] More preferably, the carbonization temperature is 900-1600° C., and the carbonization time is 1-20 h.
[0046] Those skilled in the art will appreciate that by adjusting carbonization conditions such as temperature and time, the performance of the negative electrode material can be optimized, such as the capacity and first coulombic efficiency (first efficiency) of the negative electrode material.
[0047] Furthermore, the carbonization is carried out under the protection of an inert gas (such as nitrogen).
[0048] The second aspect of the present invention provides a coal-based negative electrode material prepared by the above preparation method.
[0049] In order to better understand the technical solution of the present invention, the present invention is described in detail below in conjunction with specific embodiments.
[0050] (1) Coal petrology analysis
[0051] According to the national standards GB / T 16773-2008 (method for preparing samples for coal petrology analysis) and GB / T8899-2013 (method for determining the microscopic components and minerals of coal), the selected coal was subjected to coal petrology analysis. When calculating the vitrinite content, inertinite content and exinite content in the coal, the mineral groups in the microscopic components were not considered, and only the sum of the contents of vitrinite, inertinite and exinite was taken as 100% of the total amount.
[0052] That is, the calculation method of the inertin content is M 惰质组 / (M 镜质组 +M 惰质组 +M 壳质组 ),
[0053] Among them, M 惰质组 is the volume content of inertinite in the coal macerals, M 镜质组 is the volume content of vitrinite in the coal macerals, M 壳质组 It is the volume content of exinite in the coal maceral components.
[0054] (2) Particle size (D 50 )
[0055] Particle size D 50 , tested by Malvern Mastersizer 2000 laser particle size analyzer produced by Malvern Instruments Ltd., UK.
[0056] (3) Battery performance
[0057] The charge and discharge capacity (capacity) and first coulomb efficiency (first efficiency) of the battery were tested by using the battery test system CT2001A battery tester of Wuhan Blue Electric Electronics Co., Ltd., with a current of 0.1C (1C=300mAh / g) and a voltage of 0-3V.
[0058] In some embodiments, the coal samples AF are coal samples selected from different coal mines and coal seams, which are used for coal petrological analysis and preparation of coal-based negative electrode materials after ash removal.
[0059] Example 1
[0060] The preparation of coal-based negative electrode materials includes the following steps:
[0061] (1) Coal petrology analysis
[0062] Coal petrological analysis of coal sample A (excluding 3.0% of the mineral group in the microscopic components) showed that the vitrinite content was 58.6%, the inertinite content was 41.4%, and the exinite content was 0%.
[0063] (2) Coal ash removal
[0064] Coal sample A was deashed using a conventional acid-base method (HCl / NaOH). The ash content of the deashed coal was 0.07%. The specific steps were as follows:
[0065] Mix 400g of coal sample A, 700g of sodium hydroxide and 400ml of water, knead and react at 150°C for 3h, add water to cool down, filter and wash to obtain alkaline deashed coal;
[0066] According to the acid-coal ratio of 1:1 (volume / weight ratio of concentrated hydrochloric acid to alkaline deashed coal), dilute hydrochloric acid of 10 wt.% is added to the alkaline deashed coal, and the mixture is stirred for reaction at 60°C for 0.5h, filtered, washed and dried to obtain deashed coal.
[0067] (3) Preparation of coal-based negative electrode materials
[0068] The deashed coal was ground using a drum ball mill to obtain D 50 =7μm deashing coal particles;
[0069] Under nitrogen protection, the deashed coal particles were carbonized in a horizontal carbonization furnace at 1200°C for 3 hours to obtain coal-based negative electrode materials.
[0070] (4) Performance testing
[0071] Coal-based negative electrode materials are used as the main raw materials to prepare negative electrode sheets, and sodium-ion batteries are assembled to test capacity and initial efficiency.
[0072] Example 2
[0073] The difference from Example 1 is that the object of coal petrological analysis in step (1) is coal sample B (excluding 5.1% of the mineral group in the microscopic components), which has a vitrinite content of 46.9%, an inertinite content of 50.0%, and an exinite content of 3.1%;
[0074] The ash content of the deashed coal in step (2) is 0.08%.
[0075] Example 3
[0076] The difference from Example 1 is that the object of coal petrological analysis in step (1) is coal sample C (excluding 2.3% of the mineral group in the microscopic components), whose vitrinite content is 38.3%, the inertinite content is 56.4%, and the exinite content is 5.3%.
[0077] The ash content of the deashed coal in step (2) is 0.07%.
[0078] Example 4
[0079] The difference from Example 1 is that the object of coal petrological analysis in step (1) is coal sample D (excluding 1.8% of the mineral group in the microscopic components), which has a vitrinite content of 36.3%, an inertinite content of 62.8%, and an exinite content of 0.9%;
[0080] The ash content of the deashed coal in step (2) is 0.06%.
[0081] Example 5
[0082] The difference from Example 1 is that the object of coal petrological analysis in step (1) is coal sample E (excluding 2.1% of the mineral group in the microscopic components), which has a vitrinite content of 29.2%, an inertinite content of 70.2%, and an exinite content of 0.6%;
[0083] The ash content of the deashed coal in step (2) is 0.05%.
[0084] Example 6
[0085] The difference from Example 5 is that step (2) adopts conventional acid-base method (HNO3 / NaOH) for deashing, and concentrated hydrochloric acid is replaced by concentrated nitric acid; the ash content of the deashed coal is 0.05%.
[0086] The particle size D of the ball milling treatment in step (3) 50 5μm.
[0087] Example 7
[0088] The difference from Example 5 is that in step (2), conventional acid-base method (H2SO4 / NaOH) is used for deashing, and concentrated hydrochloric acid is replaced by concentrated sulfuric acid. The ash content of the deashed coal is 0.35%.
[0089] The particle size D of the ball milling treatment in step (3) 50 5μm.
[0090] Example 8
[0091] The difference from Example 5 is that step (2) uses hydrofluoric acid method (HF / HCl) to remove ash, and the ash content of the removed coal is 0.06%. The specific steps are:
[0092] Take 400g of coal sample E, add 1000ml of 4% hydrofluoric acid, react at room temperature for 1h and filter, add 1000ml of 5% hydrochloric acid to the filter cake, react at 60℃ for 1h and filter, wash and dry the filter cake to obtain deashed coal;
[0093] The particle size D of the ball milling treatment in step (3) 50 5μm.
[0094] Example 9
[0095] The difference from Example 5 is that the particle size D of the ball milling treatment in step (3) is 50 The carbonization conditions are 900℃ and 16h.
[0096] Example 10
[0097] The difference from Example 5 is that the particle size D of the ball milling treatment in step (3) is 50 The carbonization conditions are 1600℃ and 1h.
[0098] Comparative Example
[0099] The difference from Example 1 is that the object of coal petrological analysis in step (1) is coal sample F, whose vitrinite content is 65.9%, inertinite content is 34.1%, and exinite content is 0%.
[0100] Test Case
[0101] The coal-based negative electrode material obtained in the embodiment and the comparative example is mixed evenly with the conductive carbon black Super P and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 92:3:5, and the solvent N-methylpyrrolidone (NMP) is added to stir into a negative electrode slurry, which is evenly coated on the aluminum foil and dried to obtain a negative electrode sheet. The negative electrode sheet is punched into a sheet with a diameter of 12 mm, transferred to an MBraun2000 glove box (Ar atmosphere), and assembled into a button cell with a metal sodium sheet as a reference electrode. The charge and discharge capacity (capacity) and the first coulomb efficiency (first efficiency) of the button cell are tested, and the test results are shown in Tables 1 and 2.
[0102] Table 1:
[0103]
[0104]
[0105] Table 2:
[0106]
[0107] It can be seen from Table 1 that after deducting the mineral group, the higher the inert group content in the coal, the higher the capacity and first efficiency of the coal-based negative electrode material prepared after ash removal, that is, the better the performance. When the inert group content is greater than 40%, the capacity and first efficiency of the coal-based negative electrode material are significantly improved. When the inert group content is greater than 70%, the capacity of the obtained coal-based negative electrode material is greater than 300mAh / g, and the first efficiency is greater than 90%.
[0108] It can be seen from Examples 5-8 in Table 2 that the screened coal provided by the present invention is deashed by different chemical methods. When the ash content in the deashed coal is relatively high, the capacity and first efficiency of the prepared coal-based negative electrode material are low. When the ash content in the coal is reduced to below 0.1%, the capacity and first efficiency of the negative electrode material can be significantly improved. It can be seen from Examples 9 and 10 that carbonization at a higher or lower temperature within the range specified by the present invention, and ball milling with a particle size that is too large or too small, will reduce the capacity and first efficiency of the negative electrode material.
Claims
1. A method for preparing a coal-based negative electrode material, characterized in that: The steps include: (1) Coal with an inert content of more than 40% in its maceral components is used as screening coal; (2) deashing the screened coal to obtain deashed coal; (3) Carbonizing the deashed coal to obtain a coal-based negative electrode material.
2. The method for preparing a coal-based negative electrode material according to claim 1, characterized in that: The coal microscopic components in step (1) are the components of coal under a microscope, including vitrinite, inertinite, exinite and mineral group; The inert group content in step (1) is given by the formula M 惰质组 / (M 镜质组 +M 惰质组 M 壳质组 ) calculation, where M 惰质组 is the volume content of inertinite in the coal macerals, M 镜质组 is the volume content of vitrinite in the coal macerals, M 壳质组 It is the volume content of exinite in the coal maceral components.
3. The method for preparing a coal-based negative electrode material according to claim 1 or 2, characterized in that: The coal selected in step (1) is coal having an inertin content of greater than 50% by weight, preferably coal having an inertin content of greater than 60% by weight.
4. The method for preparing a coal-based negative electrode material according to claim 1 or 2, characterized in that: The coal screened in step (1) is coal having an inert group weight content greater than 70%.
5. The method for preparing a coal-based negative electrode material according to claim 1, characterized in that: The ash removal method in step (2) is chemical ash removal, or a combination of physical and chemical ash removal.
6. The method for preparing a coal-based negative electrode material according to claim 1 or 5, characterized in that: The ash content of the deashed coal in step (2) is less than 0.5%, preferably less than 0.2%, and more preferably less than 0.1%.
7. The method for preparing a coal-based negative electrode material according to claim 1, characterized in that: In the step (3), the carbonization temperature is 900-1600° C., and the carbonization time is 1-20 h.
8. The method for preparing a coal-based negative electrode material according to claim 1 or 7, characterized in that: In the step (3), the deashed coal is ground before the carbonization or after the carbonization.
9. A coal-based negative electrode material prepared by the method as described in any one of claims 1 to 8.
10. The coal-based negative electrode material according to claim 9, characterized in that: The particle size D of the coal-based negative electrode material 50 1-100 μm, preferably 3-25 μm.
Citation Information
Patent Citations
Sodion secondary battery negative electrode material and preparing method and application thereof
CN105185997A
Amorphous carbon material and preparation method thereof, sodium ion battery negative electrode and sodium ion battery
CN113493193A
Negative electrode material, preparation method thereof and battery
CN114789998A
Method for preparing activated carbon of high-specific capacitance super capacitor
CN102101668A
Coal-based carbon negative electrode material, preparation method and application thereof, and battery containing coal-based carbon negative electrode material
CN114335522A